Withdrawal Interval Estimation of Doxycycline in Yellow Catfish (Pelteobagrus fulvidraco) Using an LC-MS/MS Method Based upon QuEChERS Sampling Preparation - Ning Xu (MDPI AG, 2021)
Limited information on residue depletion of doxycycline (DC) is available in yellow catfish (Pelteobagrus fulvidraco) using the determination of LC-MS/MS based upon a rapid and simple method of sample preparation. This study collected plasma and tissue samples of yellow catfish at pre-determined time points following 3-day consecutive oral administration of DC at 20 mg/kg. The samples were prepared using a QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) approach. The limit of detection and the limit of quantitation were 2.5 and 5 µg/kg or µg/L, respectively, for DC in plasma and tissues (e.g., muscle + skin, liver, kidney, and gill). The recoveries of DC ranged from 67.2% to 86.2%. The decision limit (CCα) and the detection capability (CCβ) were from 106.2 to 127.8 μg/kg or μg/L. The withdrawal times of DC in muscle + skin were estimated to be 22 d based on the guidelines in China and Europe and 27 d based on Japan’s standard. Overall, this study not only provides an efficient method to rapidly determine the DC concentrations in fish-derived tissues but also provides important information on the safety assessment of DC in aquatic animal-derived food products.